Spring migration 1971, Red Rock Refuge and Pleasantville area, Marion County, Iowa - Black, Gladyset al (1971)
Field notes from Gladys Black was regarding birds she sighted at Red Rock Refuge and the Pleasantville area in Marion County, Iowa, during the spring migration of 1971, dated May 25, 1971. Some bird names were circled in red: Little Blue Heron, Willet, Black-bellied and Golden Plover, Dunlin, Hudsonian Godwit, and Caspian Tern. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1971. Epson - sheet feed/flatbed